The relationship between maximal aerobic power and recovery in elite ice hockey players during a simulated game - Steeves, D.; Campagna, P. (The Journal of Strength and Conditioning Research, 2019)
This project investigated whether there was a relationship between maximal aerobic power and the recovery or performance in elite ice hockey players during a simulated hockey game. An on-ice protocol was used to simulate a game of ice hockey. Recovery values were determined by the differences in lactate and heart rate measures. Total distance traveled was also recorded as a performance measure. On 2 other days, subjects returned and completed a maximal aerobic power test on a treadmill and a maximal lactate test on ice. Statistical analysis showed no relationship between maximal aerobic power or maximal lactate values and recovery (heart rate, lactate) or the performance measure of distance traveled. It was concluded that there was no relationship between maximal aerobic power and recovery during a simulated game in elite hockey players.